Journal of Political Economy (Journal of Political Economy, 2017)
Previous articleNext article FreeJournal of Political EconomyPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Jason AbaluckAnat AdmatiMohammad AkbarpourHunt AllcottDouglas AlmondManuel AmadorSiwan AndersonCristina ArellanoCostas ArkolakisEnghin AtalayYu AwayaMiguel BallesterOriana BandieraAlan BarenbergSamuel BazziAlberto BisinGustavo BobonisBen BrooksJennifer BrownLeonardo BursztynLuis CabralCharles CalomirisGabriel CarrollDavid ChanAndrew ChingGabe Chodorow-ReichJohn ClitheroOlivier CoibionFabrice CollardAnna CostelloArnaud CostinotVictor CoutureLucas DavisJan De LoeckerMark DeanMelissa DellDave DonaldsonRoss DoppeltDavid DornChristian DustmannPawel DziewulskiLena EdlundJan EeckhoutMehmet EkmekciJoan EstebanBenjamin FaberRaquel FernandezFernando FerreiraDavid FiglioFrederico FinanAmy FinkelsteinRaymond FismanMarco FrancesconiPatrick FrancoisBrigham FrandsenPeter FredrikssonJoshua GansAlessandro GavazzaAhu GemiciCorrado GiuliettiEdward GlaeserLimor GolanBart GolsteynYuriy GorodnichenkoJoshua GottliebJesse GregoryVeronica GuerrieriLuigi GuisoJonathan GuryanMarina HalacJoseph HarringtonGlenn HarrisonGuojun HeAaron HedlundEskil HeinesenRichard HornbeckThomas HubbardIl-Myoung HwangKelsey JackC. Kirabo JacksonBas JacobsSimon JaegerJoonhwi JooLisa KahnNavin KartikJakub KastlTim KautzTobias KleinPeter KlenowHenrik KlevenGeorgi KocharkovRalph KoijenScott KominersHideo KonishiFabian KosseRachel KrantonKory KroftPeter KuhnNicola LaceteraDarius LakdawallaThibaut LamadonKevin LangFabian LangeJennifer La’OBrad LarsenStephan LauermannVictor LavyBenjamin LesterSoren Leth-PetersenMatthew LewisClaire LimNuno LimaoXiliang LinLance LochnerJens LudwigW. Bentley MacLeodThierry MagnacNeale MahoneyOfer MalamudIvan MarinovicGregory MartinEoin McGuirkPascal MichaillatRobert MillerKurt MitmanHolger MuellerCaitlin MyersPaulo NatenzonJ. NearyDavid NeumarkJuan NicoliniVolker NockeEd NosalMatthew NotowidigdoBenjamin OlkenEmily OsterHyunmin ParkJonathan ParkerJohn PattyAmil PetrinAndrea PratDrazen PrelecVictoria ProwseSteven PullerValerie RameyJoshua RauhDevesh RavalMichelle RendallWilliam RoberdsMaria Rosales-RuedaMarzena RostekChristoph RotheJesse RothsteinYona RubinsteinAldo RustichiniPeter SavelyevAnalia SchlosserMartin SchmalzAnanth SeshadriAzeem ShaikhKelly ShueRon SiegelEric SimsTodd SinaiAloysius SiowScott SternPhilipp StrackBruno StruloviciTomasz StrzaleckiMartin StuermerJavier SuarezAdi SunderamAshley SwansonChristopher TaberDuncan ThomasChristopher TimminsPetra ToddFrancesco TrebbiRaluca UrsuStijn Van NieuwerburghGreg VeramendiMiguel Villas-BoasGabor ViragFabian WaldingerChristopher WaltersFrederic WarzynskiYasutora WatanabeRebecca Weitz-ShapiroBirger WernerfeltMichael WhinstonMatthew WiswallAlexander WolitzkyChristopher WoodruffDaniel Yi XuFlorian ZettelmeyerCharles ZhengEkaterina ZhuravskayaSeth ZimmermanEric Zwick Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 125, Number 5October 2017 Article DOIhttps://doi.org/10.1086/695313 Views: 1125Total views on this site © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.